1996
DOI: 10.1093/oxfordjournals.annonc.a010601
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for carcinoma of the esophagus: A comparison of evidence from meta-analyses of randomized trials and of historical control studies

Abstract: There was a gross overestimation of treatment effect in the studies using HC as compared to RCTs, despite the use of cisplatinum-based chemotherapy in both groups. The meta-analysis of RCTs reveal no significant survival benefit from cisplatinum-based adjuvant/neoadjuvant chemotherapy in esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
6

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 19 publications
0
24
0
6
Order By: Relevance
“…Earlier comparative (observational) studies using historical controls overestimated the benefits of chemotherapy [7], whereas individual RCTs from the 1990s failed to find a significant advantage in terms of overall survival with neoadjuvant chemotherapy. Two major randomized studies, the Intergroup 113 [8] and the Medical Research Council (MRC) [9] studies showed conflicting results-the former showing no difference and the latter showing a benefit with NACT.…”
Section: Neoadjuvant Chemotherapy Plus Surgery Versus Surgery Alonementioning
confidence: 97%
“…Earlier comparative (observational) studies using historical controls overestimated the benefits of chemotherapy [7], whereas individual RCTs from the 1990s failed to find a significant advantage in terms of overall survival with neoadjuvant chemotherapy. Two major randomized studies, the Intergroup 113 [8] and the Medical Research Council (MRC) [9] studies showed conflicting results-the former showing no difference and the latter showing a benefit with NACT.…”
Section: Neoadjuvant Chemotherapy Plus Surgery Versus Surgery Alonementioning
confidence: 97%
“…There does not appear to be any notable survival benefit of adjuvant chemotherapy [13] in esophageal cancer. The addition of adjuvant chemoradiotherapy (CRT) to surgery in cases of EGJ and gastric adenocarcinoma was investigated in the INT-0116 phase III trial [14]; adjuvant CRT was reported to give a survival benefit over surgery alone, but the advantage of postoperative treatment was questionable if adequate surgery was performed [15].…”
Section: Neoadjuvant Therapy: Chemotherapy Versus Chemoradiotherapymentioning
confidence: 90%
“…Adjuvant therapy may be difficult in this disease. A recent meta-analysis by Bhansali et al (1996) of 12 randomized clinical trials and eight with historical controls revealed no significant survival benefit from cisplatin-based adjuvant/ neoadjuvant chemotherapy in oesophageal cancer.…”
Section: Concomitant Chemotherapy In the Preoperative Settingmentioning
confidence: 99%